Wahdat al-Wujūd, Pesantren, and Religious Moderation Model in Indonesia - Syamsul Huda; Iqbal Hamdan Habibi (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
This article is based on a research on religious moderation in Pesantren (Islamic Boarding School) reviewed from the perspective of Ibn Arabi. It focuses on the violation of belief and religious freedom (KKB) in Indonesia, with its intensity through coercion and subjective judgement against other beliefs and sects. This study aims to relate wahdat al-wujūd, the concept of Ibn Arabi, with religious moderation concept in pesantren. This study found that (1) the concept of wahdat al-wujūd has philosophically constructed moderate mental and mindset; (2) pesantrens are able to instill the concept of religious moderation into students through their educational system; and (3) through wahdat al-wujūd Ibn Arabi proposes unifying concept and the nature of human being supporting the existence of religious moderation.